Balancing the trade-offs between land productivity, labor productivity and labor intensity - Cristina Chiarella; Patrick Meyfroidt; Dilini Abeygunawardane; Piero Conforti (Ambio, 2023)
Agricultural intensification, through increased yields, and raising incomes, through enhanced labor productivity, are two dimensions prioritized for sustainable agricultural development. Prioritizing these two outcomes leaves labor intensity as a hidden adjustment variable. Yet, when agriculture is mainstay and the prospects of labor absorption in other sectors are scarce, the density of agricultural employment is central for livelihoods. We revise relationships of land and labor productivity and labor intensity with farm size, using standardized data for 32 developing countries. We show that labor productivity increases with farm size, while land productivity and labor intensity decrease with farm size nonlinearly. Technical efficiency increases with farm size. We further systematize the evidence on how, beyond the farm level, local contexts can be pivotal in choosing how to prioritize the dimensions of the trade-off space. Our findings contribute to debates on the fate of small-scale farmers, and call for contextualized decisions.
Keywords: 630; agricultural productivity; farm size; labor intensity; policy decision making; technical efficiency